ONLINE AGGRESSION TENDENCIES AND COGNITIVE EMPATHY TOWARDS THE VICTIM OF CYBERBULLYING IN ADOLESCENTS - Dana BALAS TIMAR (Cross-Cultural Management Journal, 2018)

(untitled)
Empathy is an adaptive phenomenon in the act of inter-human communication, allowing a certain way of entering the psychology of the other as a means of elaborating own behaviour pattern. Through empathy, we have the opportunity to better understand the other, to intuitively sense alterity’s thoughts and affections, to anticipate behaviour and even to act accordingly. In real, as in online environments, there are always two sides of this story, the best part is when the communication intention is good and the worst part is when manipulation interferes and the empathy serves to better understand victim’s weaknesses to better use it against them. Our research team has developed the project Keeping youth safe from Cyberbullying, ID 2016-3-TR01-KA205-036619 aiming to deeper understand the dynamics of different cyberbullying aspects in online environments among youth, by creating an online questionnaire assessing core concepts and perceptions about cyberbullying motives and effects. Our focus is in analysing the effects of aggression tendencies on victim cognitive empathy in cyberbullying incidents, in 140 high school students. This research’s conclusion brings an answer to the question of just how much empathy is needed for understanding cyberbullying victim’s feelings and activating a prosocial behaviour instead of turning it into a cruel act of psychological dominance all over the online pavement.